Buckling of functional graded polymeric sandwich panel under different load cases - Uysal, Mine Uslu; Guven, Ugur (ELSEVIER SCI LTD, 2015)
In the present paper, the buckling behaviors of adhesively bonded sandwich plates subjected to in-plane shear force, in-plane normal compression force, and out-of-plane distributed load were studied for both point supported concept and linear supported concept. The functionally gradient polymeric adherends and elastic, homogeneous adhesive were used in the assembly. The epoxy resin was used and two types of graphite powder materials were selected PAM96/98 and PV60/65 as filler. The graphite powders were added to the epoxy resin as 3%, 6%, 9%, and 12% vol. The structure and graphite distribution were investigated by light microscope and the elasticity modulus of adherends were predicted based on the image processing program. The influences of the type and volume of graphite powders on the buckling behavior were studied by finite element analyses. The critical buckling loads were predicted and their mode shapes were presented. The highest critical buckling load was determined in PV60/65 structure panels for three different load cases due to the fact that the PV60/65 graphite powder was compatible with epoxy resin. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Sandwich structure; Functionally graded polymeric materials (FGPMs); Buckling; Finite element analysis (FEA); COMPOSITE; NANOCOMPOSITES; PLATES; Mechanics; Materials Science